Lipidome LC/MS Analysis in the Insect Adaptation and Development Studies - Tomčala, Aleš (Jihočeská univerzita, 2009)
Insects represent very useful experimental model in various branches of biological research. The investigation is driven by economic importance of many insect species, and also by biological features of insects as model organisms such as short period of reproduction, easy breeding and manipulation and, in particular, the minimal regulatory requirements which are associated to the management of vertebrates. Here we report robust and efficient LC/MS/MS methodology for the determination of the physiologically important lipid molecular species in insects. The target metabolites represent polar glycerophos-phopholipids (GPL) and nonpolar lipids diacylglycerols (DG) and triacylglycerols (TG). Combination of the LC/MS data with the subsequent GC fatty acid analysis enables complete structural elucidation of particular lipid species including their fatty acid compositions. The developed methodology was applied to studies of the chill tolerance of the firebug Pyrhocorris appterus. Fields and laboratory experiments were conducted to separate the triggering effects of low temperature, desiccation and diapause progression on the physiological characteristics related to chill tolerance with emphasis on the restructuring of GPL composition. The same effect on the GPL composition was observed during acclimatization in the field and cold acclimation in laboratory. By contrast, the GPL changes related to desiccation and diapause progression were relatively small (Tomčala et al, 2006). In adults of Drosophila melanogaster it has been found that acclimation at 15, 20 and 25°C during preimaginal development affects thermal tolerance and composition of membrane GPLs. Low temperature acclimation was associated with increase in proportion of ethanolamine at the expense of choline in GPLS. Relatively small, but statistically significant changes in lipid molecular compositon were observed with decreasing acclimation temperature (Overgard et al, 2008). Hormonal treatment studies on insect model Locusta migratoria showed a heterogeneous distribution of individual DGs in haemolymph after the hormone application and revealed that mobilization of the DGs is molecular species-specific with the highest proportion of DG 16:0/18:1 and forming in summary about 20% of the total mobilized DG content. Additional analysis of fat body triacylglycerols revealed that the AKH mobilizes the DGs specifically with the preference of those possessing the unsaturated C18 fatty acids (FAs). The fat body FAs with more than 18 carbons did not participate on the mobilization (Tomcala et al, 2009). The LC/MS methodology was further applied to lipid composition studies of several samples with very diverse biological origin (fish, human blood etc.) and was proved to be universally applicable to the wide scope of biological samples.
Lipidome LC/MS Analysis in the Insect Adaptation and Development Studies
Keywords: Glycerolipids; ESI/MS; LC/MS; HPLC.